Enterprise risk management practices in listed croatian companies - Danijela Milos Sprcic; Ena Pecina; Silvije Orsag (UTMS Journal of Economics, 2017)
The purpose of this research is to (1) explore Enterprise Risk Management (ERM) practices in Croatian companies, (2) establish ERM maturity Index, (3) define level of ERM development of Croatian companies, (4) analyse organizational aspect of risk management, methods of risk assessment and types of risk managed in Croatian companies. With that aim, conceptual research combined with survey among top management in Croatian listed companies was conducted. Based on the results it can be concluded that ERM is mainly underdeveloped in Croatian companies. Most of the analysed companies have low values of ERM Index, with intimidating 38% of companies not having any of ERM system elements. The most worrying result is that even 28% of analysed companies do not manage risks at all. Many important types of risks are neglected, so as methods of risk measurement are simple and outdated. Contribution of this paper is twofold. This is the first research conducted to explore ERM practices in detail, in which ERM Index as a measure of the maturity of ERM process is developed. Secondly, this paper brings recommendations to Supervisory and Management Board, as well as to Regulators, which could initiate broader ERM implementation and development in Croatian companies.
Keywords: G32; G39; 330; Enterprise Risk Management; ERM maturity Index; Risk Management practices